Harmonic Contrast-Enhanced Endoscopic Ultrasonography for the Guidance of Fine-Needle Aspiration in Solid Pancreatic Masses - Seicean, Andrada; Badea, Radu; Moldovan-Pop, Anca; Vultur, Simona; Botan, Emil Claudiu; Zaharie, Teodor; Săftoiu, Adrian; Mocan, Teodora; Iancu, Cornel; Graur, Florin; Sparchez, Zeno; Seicean, Radu (Ultraschall in der Medizin - European Journal of Ultrasound, 2017)
Purpose The global accuracy of fine-needle aspiration guided by endoscopic ultrasound (EUS-FNA) for pancreatic adenocarcinoma is about 85 %. The use of contrast agents during EUS to highlight vessels and the necrotic parts of pancreatic masses may improve biopsy guidance. Our aim was to assess whether the guidance of FNA by harmonic contrast-enhanced endoscopic ultrasound (CH-EUS) would increase diagnostic accuracy relative to conventional EUS-FNA in the same pancreatic masses.Patients and Methods In a prospective study, EUS-FNA was performed in patients with pancreatic masses on CT scan, followed by harmonic CH-EUS using SonoVue. A second cluster of CH-EUS-FNA was performed on contrast-enhanced images. The final diagnosis was based on the results of EUS-FNA and surgery, or the findings after 12 months’ follow-up.Results The final diagnosis was adenocarcinoma (n = 35), chronic pancreatitis (n = 10), or other (n = 6). The diagnostic accuracy based on core histology was 78.4 % for EUS-FNA and 86.5 % for CH-EUS-FNA (p = 0.35). The accuracy increased to 94 % when the two methods’ results were combined. The two false-negative EUS-FNA cases were correctly appreciated by CH-EUS. Neither core histology size nor the presence of necrosis was significant for the true-positive diagnosis of malignancy.Conclusion CH-EUS-FNA had an insignificant incremental effect on diagnostic accuracy compared with conventional EUS-FNA in our small group. The presence of necrosis did not influence the results of CEUS-FNA. Qualitative assessment of the contrast uptake within the lesion was useful in false-negative EUS-FNA cases.
Keywords: pancreas; contrast agents; endosonography; neoplasms; fine-needle aspiration